2021
DOI: 10.3389/fpls.2021.738119
|View full text |Cite
|
Sign up to set email alerts
|

Power and Weakness of Repetition – Evaluating the Phylogenetic Signal From Repeatomes in the Family Rosaceae With Two Case Studies From Genera Prone to Polyploidy and Hybridization (Rosa and Fragaria)

Abstract: Plant genomes consist, to a considerable extent, of non-coding repetitive DNA. Several studies showed that phylogenetic signals can be extracted from such repeatome data by using among-species dissimilarities from the RepeatExplorer2 pipeline as distance measures. Here, we advanced this approach by adjusting the read input for comparative clustering indirectly proportional to genome size and by summarizing all clusters into a main distance matrix subjected to Neighbor Joining algorithms and Principal Coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
2
6
0
Order By: Relevance
“…In agreement with previous studies from other angiosperms (Dodsworth et al, 2015;McCann et al, 2018McCann et al, , 2020Vitales et al, 2020b;Herklotz et al, 2021), the different amounts of shared repeats retrieved from comparative RE2 analyses of Loliinae have been shown to contain phylogenetic information at different systematic levels across the four Loliinae evolutionary groups. All evolutionary analyses have confirmed their ability to recover deep-to-shallow evolutionary relationships that were highly or relatively consistent with those based on the 35S rDNA and the plastome and combined data sets, respectively (Tables 1, 4, Figures 4, 5, Supplementary Tables 3, 4, and Supplementary Figures 1, 3).…”
Section: Phylogenetic Value Of the Loliinae Repeatome And Deconvoluti...supporting
confidence: 88%
See 1 more Smart Citation
“…In agreement with previous studies from other angiosperms (Dodsworth et al, 2015;McCann et al, 2018McCann et al, , 2020Vitales et al, 2020b;Herklotz et al, 2021), the different amounts of shared repeats retrieved from comparative RE2 analyses of Loliinae have been shown to contain phylogenetic information at different systematic levels across the four Loliinae evolutionary groups. All evolutionary analyses have confirmed their ability to recover deep-to-shallow evolutionary relationships that were highly or relatively consistent with those based on the 35S rDNA and the plastome and combined data sets, respectively (Tables 1, 4, Figures 4, 5, Supplementary Tables 3, 4, and Supplementary Figures 1, 3).…”
Section: Phylogenetic Value Of the Loliinae Repeatome And Deconvoluti...supporting
confidence: 88%
“…Several studies have demonstrated that similarity-based clustering of low coverage genome sequencing reads, which confidentially represent 0.50-0.01× of the total haploid genome coverage, is proportional to the genomic abundance and longitude of the corresponding repeat-types (Macas et al, 2015;Pellicer et al, 2018) and could therefore be used to quantify them. The utility of the Repeat Explorer 2 bioinformatics tools for the quantification and annotation of repeats in plants (Novák et al, 2020) has been implemented by phylogenetic and distance-based network methods and by multivariate statistical methods that have corroborated the phylogenetic signal of the repeatome in various groups of angiosperm (Vitales et al, 2020a,b;Herklotz et al, 2021). It has also been supplemented by 5S rDNA graphbased clustering methods which have successfully corroborated the identity of the ancestral progenitor genomes of several polyploid plants (Garcia et al, 2020;Vozárová et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is often observed that genomic repeat profiles contain a phylogenetic signal (Dodsworth et al ., 2015; McCann et al ., 2020; Vitales et al ., 2020b; Herklotz et al ., 2021). In the case of Beta and Patellifolia species, this is only partly true: Overall, the repeatomes enable to separate the beet species into genera and sections.…”
Section: Discussionmentioning
confidence: 99%
“…It is often observed that genomic repeat profiles contain a phylogenetic signal (Dodsworth et al., 2015; Herklotz et al., 2021; McCann et al., 2020; Vitales, Garcia, & Dodsworth, 2020). In the case of Beta and Patellifolia species, this is only partly true: Overall, the repeatomes enable to separate the beet species into genera and sections.…”
Section: Discussionmentioning
confidence: 99%